1994
DOI: 10.1080/01904169409364790
|View full text |Cite
|
Sign up to set email alerts
|

A solution culture study of manganese‐tolerant and ‐sensitive tobacco genotypes

Abstract: Genotypic differences in tolerating toxic levels of heavy metals have been observed in various plant species. This research was conducted to study the effect of manganese (Mn), iron (Fe), calcium (Ca), and magnesium (Mg) accumulation on two tobacco genotypes, Tobacco Introduction (T.I.) 1112 and KY 14, that have exhibited different sensitivity to toxic levels of Mn. The investigation was carried out employing a solution culture technique in which combinations of three levels of Mn exposure at varying strengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Excess Mn induces inhibition of chlorophyll biosynthesis and a decline in the photosynthetic rate (Macfie and Taylor, 1992;Hauck et al, 2002). The responses of plants to excessive Mn availability depend not only on the exact Mn concentration in the root zone, but also on temperature (Rufty et al, 1979), levels of other nutrients in the root zone (Wang et al, 1994), and light intensity (Nable et al, 1988). It has been reported that cucumber plants grown under high-light conditions display lower net photosynthesis and develop more serious symptoms of Mn toxicity than plants grown under low-light conditions (Shi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Excess Mn induces inhibition of chlorophyll biosynthesis and a decline in the photosynthetic rate (Macfie and Taylor, 1992;Hauck et al, 2002). The responses of plants to excessive Mn availability depend not only on the exact Mn concentration in the root zone, but also on temperature (Rufty et al, 1979), levels of other nutrients in the root zone (Wang et al, 1994), and light intensity (Nable et al, 1988). It has been reported that cucumber plants grown under high-light conditions display lower net photosynthesis and develop more serious symptoms of Mn toxicity than plants grown under low-light conditions (Shi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type of enzyme, the concentration of exogenous metal, and plant growth stage, there are different effects (promotion or inhibition) on enzyme activity [15][16][17]. When metal ion enters plants, they can bind to active or inactive sites on biomolecules, which changes physiological and metabolic functions, causing poisoning and even plant death [18].…”
Section: Introductionmentioning
confidence: 99%